Agile Processes in Software Engineering and Extreme Programming 19th International Conference, XP 2018, Porto, Portugal, May 21-25, 2018, Proceedings - Garbajosa, Juan; Wang, Xiaofeng; Aguiar, Ademar (Lecture Notes in Business Information Processing,, 2018)
This open access book constitutes the proceedings of the 19th International Conference on Agile Software Development, XP 2018, held in Porto, Portugal, in May 2018. XP is the premier agile software development conference combining research and practice, and XP 2018 provided a playful and informal environment to learn and trigger discussions around its main theme - make, inspect, adapt. The 21 papers presented in this volume were carefully reviewed and selected from 62 submissions. They were organized in topical sections named: agile requirements; agile testing; agile transformation; scaling agile; human-centric agile; and continuous experimentation. .